ANÁLISE DA QUALIDADE AMBIENTAL DOS REMANESCENTES DE CERRADO NA BACIA HIDROGRÁFICA DO RIO DO POMBO, EM TRÊS LAGOAS (MS). - MARIA DO CARMO RODRIGUES BARBOSA (2024)
The objective of the present work was investigate the fragmentation of the Cerrado biome in the Rio do Pombo Hydrographic Basin, considering the impacts of changes in land use and occupation. The Brazilian Cerrado has suffered several environmental impacts in recent decades due to inadequate soil exploitation and predatory practices, resulting in the continuous reduction of native vegetation areas. These remaining areas have been fragmented into disconnected portions, often with ecologically irrelevant sizes and low environmental quality. The research focused on analyzing the environmental quality of the Cerrado remnants in the Rio do Pombo Basin, located in the context of the Paraná River Basin, in the municipality of Três Lagoas-MS. The study unit was the river basin, using a theoretical and methodological approach based on geotechnology. Primary data were collected and indicators of environmental quality were applied, such as size of the remnant, circularity index, distance from the nearest neighbor, proximity to watercourses and highways, slope, hypsometry and NDVI index, in addition to morphometric characterization and creation of thematic maps of the area. The Pombo River Basin covers an area of 2,074.94 km², with altitude variation between 278 and 529 meters. The analysis of the 53 Cerrado remnants identified that 41 of them had low environmental quality, while only one fragment, number 7, located close to the Rio do Pombo, was classified as having very high environmental quality. Differences in the quality of the remnants are linked to specific factors, such as their location and proximity to water bodies and highways. The results point to the significant degradation of Cerrado areas in the basin, especially in relation to springs, which suffer from the loss of vegetation cover and environmental quality. This compromises the ecological integrity of the region and reinforces the need for more efficient management focused on the conservation of the remnants. Connectivity between the remaining areas, however, should not be the main criterion for conservation, but rather the preservation of fragments of high environmental quality, essential for maintaining the functionality of local ecosystems.